2009
DOI: 10.1007/s10549-009-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative therapy use before and after breast cancer diagnosis: the Pathways Study

Abstract: Background-Many women use complementary and alternative medicine (CAM) to maintain or improve their health. We describe CAM use among the first 1,000 participants enrolled in the Pathways Study, an ongoing prospective cohort study of women diagnosed with breast cancer (BC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 12 publications
(13 reference statements)
8
95
3
Order By: Relevance
“…This figure is higher than the 40-43% of British adult supplement users according to two previous national UK surveys [31,32], but similar to recent findings by the Pathways study [18] reporting frequent use of botanical and other natural products by 41-58% of a cohort of 1,000 women within 5 years of their breast cancer diagnosis. In comparison to these findings earlier reports found lower pre-diagnostic supplement use by breast cancer patients which ranged from 24-33% [21,33].…”
Section: Supplement Use Before and After Diagnosissupporting
confidence: 88%
See 2 more Smart Citations
“…This figure is higher than the 40-43% of British adult supplement users according to two previous national UK surveys [31,32], but similar to recent findings by the Pathways study [18] reporting frequent use of botanical and other natural products by 41-58% of a cohort of 1,000 women within 5 years of their breast cancer diagnosis. In comparison to these findings earlier reports found lower pre-diagnostic supplement use by breast cancer patients which ranged from 24-33% [21,33].…”
Section: Supplement Use Before and After Diagnosissupporting
confidence: 88%
“…There have been few reports to date regarding behaviour changes in terms of supplement use. Holmes et al [20] found supplement users increased by 7% post-diagnosis while reports of new dietary supplement use since diagnosis range from 34-64% [2,18]. Overall, both pre-and post-diagnostic supplement use in the DietCompLyf cohort was substantial and higher than previous reports from the UK of between 33.2 and 53% for women with breast cancer [34][35][36].…”
Section: Supplement Use Before and After Diagnosismentioning
confidence: 76%
See 1 more Smart Citation
“…However, our finding is comparable with studies conducted in Malaysia, Canada, and Korea (62.5%, 71.2%, and 74.8%, resp.) [24][25][26]. The high prevalence of CAM use in our study could be partially explained by the fact that the culture in Ethiopia encourages the use of CAM especially herbal based traditional medicine and spiritual healing.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, about 20.6% of cancer patients received CAM therapies. The use of CAM therapies among patients with cancer ranged from 7-64% (1998; Richardson et al, 2000;Greenlee et al, 2009 ;Muhamad et al 2012 ;Marriam and Muhamad 2013). The large variability in CAM use between studies (from 7% to 64%) was likely to be due to the various (Bismark et al 2014).…”
Section: Discussionmentioning
confidence: 99%